Physiological Predictors of Performance on the CrossFit "Murph" Challenge - Ja'Deon D. Carreker; Gregory J. Grosicki (MDPI AG, 2020)
We examined physiological predictors of performance on the CrossFit Murph challenge (1-mile run, 100 pullups, 200 pushups, 300 air squats, 1-mile run). Male CrossFit athletes (n = 11, 27 ± 3 years) performed a battery of physical assessments including: (1) body composition, (2) upper and lower body strength, (3) upper body endurance, (4) anaerobic power, and (5) maximal oxygen consumption. No less than 72 h later, participants completed the Murph challenge, heart rate was monitored throughout, and blood lactate was obtained pre-post. Correlations between physiological parameters and total Murph time, and Murph subcomponents, were assessed using Pearson's correlations. Murph completion time was 43.43 ± 4.63 min, and maximum and average heart rate values were 185.63 ± 7.64 bpm and 168.81 ± 6.41 bpm, respectively, and post-Murph blood lactate was 10.01 ± 3.04 mmol/L. Body fat percentage was the only physiological parameter significantly related to total Murph time (r = 0.718; p = 0.013). Total lift time (25.49 ± 3.65 min) was more strongly related (r = 0.88) to Murph time than total run time (17.60 ± 1.97 min; r = 0.65). Greater relative anaerobic power (r = −0.634) and less anaerobic fatigue (r = 0.649) were related to total run time (p < 0.05). Individuals wanting to enhance overall Murph performance are advised to focus on minimizing body fat percentage and improving lift performance. Meanwhile, performance on the run subcomponent may be optimized through improvements in anaerobic power.